Dynamics and determinants of farm household income in Bihar: evidence from panel data of selected villages - KUMAR, ABHAY; SINGH, R K P; KUMAR, ANJANI; KUMAR, UJJWAL; JHA, A K; KUMAR, PANKAJ (The Indian Journal of Agricultural Sciences, 2019)
The study is undertaken to analyze the farm household income, income sources, economic inequality, and determinants of income of farm households in Bihar which is based on five-year panel data (2010–11 and 2014–15). Findings of the study show that the income level of farm households in the selected villages of Bihar is low, but exhibited an impressive annual growth rate of 6% from 2010–11 to 2014–15. The income level showed a positive relation with the size of landholding. Further, the sources of household income are quite diverse, and cultivation contributes only one-fourth to the total income of farm households. The level of remittances showed signs of decline, while the share of transfer payments and non -farm activities increased from 2010–11 to 2014–15. Inter- and intra-class inequality in farm household income is also prominent but diminishing with time. Farm assets, diversification, and education level have turned out to be important drivers of farm household income. These findings have significant implications and call for holistic rural development strategies for enhancing farmers’ income.